Apple sum

Calculus Level 3

n = 1 sin ( n ) n = ? \sum_{n=1}^∞ \frac{\sin(n)}{n} =\ ?


The answer is 1.070.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Nov 29, 2020

n = 1 sin ( n ) n = ( n = 1 e n i n ) Since e θ i = cos θ + i sin θ and ( ) = ( ln ( 1 e i ) ) is the imaginary part function. = ( ln ( 1 cos 1 i sin 1 ) ) = ( ln ( ( 1 cos 1 ) 2 + sin 2 1 e tan 1 ( sin 1 1 cos 1 ) i ) ) = ( ln ( ( 1 cos 1 ) 2 + sin 2 1 ) i tan 1 ( sin 1 1 cos 1 ) ) = tan 1 ( sin 1 1 cos 1 ) = tan 1 ( 2 t 1 + t 2 1 1 t 2 1 + t 2 ) = tan 1 ( 1 t ) Let t = tan 1 2 = tan 1 ( 1 tan 1 2 ) = 1 2 ( π 1 ) 1.07 \begin{aligned} \sum_{n=1}^\infty \frac {\sin (n)}n & = \blue \Im \left(\sum_{n=1}^\infty \frac \blue{e^{ni}}n \right) & \small \blue{\text{Since }e^{\theta i} = \cos \theta + i \sin \theta \text{ and }\Im(\cdot)} \\ & = \Im \left(-\ln \left(1-e^i \right) \right) & \small \blue{\text{is the imaginary part function.}} \\ & = - \Im \left(\ln \left(1-\cos 1 - i\sin 1 \right) \right) \\ & = - \Im \left(\ln \left(\sqrt{(1-\cos 1)^2 + \sin^2 1} \cdot e^{\tan^{-1} \left(\frac {\sin 1}{1-\cos 1}\right) i} \right) \right) \\ & = - \Im \left(\ln \left(\sqrt{(1-\cos 1)^2 + \sin^2 1}\right) - i \tan^{-1} \left(\frac {\sin 1}{1-\cos 1}\right) \right) \\ & = \tan^{-1} \left(\frac {\sin 1}{1-\cos 1} \right) = \tan^{-1} \left(\frac {\frac {2t}{1+t^2}}{1-\frac {1-t^2}{1+t^2}} \right) = \tan^{-1} \left(\frac 1t \right) & \small \blue{\text{Let }t = \tan \frac 12} \\ & = \tan^{-1} \left(\frac 1{\tan \frac 12} \right) = \frac 12 (\pi -1) \approx \boxed{1.07} \end{aligned}

Dwaipayan Shikari
Nov 29, 2020

Apple sum 🍎🍏 \textrm{Apple sum 🍎🍏}

n = 1 sin ( n ) n \sum_{n=1}^∞ \frac{\sin(n)}{n}

= n = 1 e i n e i n 2 i n = \sum_{n=1}^∞ \frac{e^{in} -e^{-in}}{2in}

1 2 i ( n = 1 e i n n e i n n ) \implies{\frac{1}{2i}(\sum_{n=1}^∞ \frac{e^{in}}{n} - \frac{e^{-in}}{n})}

1 2 i ( l o g ( 1 e i ) + l o g ( 1 e i ) ) \implies{\frac{1}{2i}(- log(1-e^i )+log(1-e^{-i}))}

So, = 1 2 i l o g ( 1 e i 1 e i ) =\frac{1}{2i} log(\frac{1-e^{-i}}{1-e^i})

= 1 2 i l o g ( e i ) = 1 2 i ( π i i ) = \frac{1}{2i} log(-e^{-i}) = \frac{1}{2i} (πi-i)

Answer is π 1 2 : ) 🍎 🍏 \boxed{\frac{π-1}{2}} :) 🍎🍏

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...